Model Alat Perajang Rumput Gajah Pakan Ternak Sapi - Sambas Prabawa (LPPM UNINUS, 2011)
Agribusiness of national dairy cows are walking towards a mainstay industry that can provide sufficient milk for people with a decent price. Therefore, raising dairy cows is stiff, it needs to be skilled with knowledge and proficiency such as maintain the shed and cows, fodder, production equipments (i.e grass chopper tool for cow fodder). Problems faced by dairy cows in the business of household scale is that less effective bulrush feeding as cows fodder, because many parts of bulrush is not eaten by cows. The undertakings have been made through the Program of Science and Technology for Society (IBM) is organizing skills training (engineering) grass chopper tool that used for feeding cattle and provisioning knowledge related to the business of dairy cows. Based on the results of cattle breeders training, they felt inspired and interested in training activities and these ideas could enrich their knowledge, insight and skills. Besides, it was related to the engine chopper performance. According to the first planning that the machine driven by biogas engines, it was having obstacles because they did not require its machine capacity, but in the end, they used conventional fuels (diesel oil). The performance earned the average of engine capacity amount 2 tons of bulrush/1.50 hours, the blade (steel) 1320 rpm, chopped length 1-10 cm, the main cost and economic value of the machine is 50% estimated lower by manually cost calculation.But one should be observed by all of us, that the finding of this bulrush chopper tool is belong to the Intellectual Property Rights (HAKI) which has potential patent on a national level.